0173 The development of a model to simulate an intra ocular bleed and lateral canthotomy. (2nd November 2015) - Credland, Tim
Abstract : Background/context: While planning stations for a regional ENT training day I was asked if it would be possible to simulate an intra ocular bleed. I asked how this presented and it was described to me as a swelling of the orbit of the eye with increasing bruising, with the eye being pushed forward as the pressure increases. The emergency treatment for this is lateral canthotomy to release the pressure from behind the eye, with the intention to save sight. Description of innovation or topic: Using a pig's head that had had its upper jaw removed (used for maxillofacial training) I investigated the entry to the rear of the orbit, with the intention of introducing a Foley catheter behind the eye. Once an entry point was found a Foley catheter was inserted and inflated, it pushed back out. The Foley was modified (the tip was removed) and reinserted, the tissue removed from the base of the head was replaced and this along with the catheter was held in place with a suture. Again the Foley catheter was inflated and the orbit appeared to swell and the eye pushed forward. To further improve this model the eyelashes were trimmed, and the third eyelid was removed, make up was then applied to the outer orbit to simulate bruising. Improvements/outcomes (anticipated or recorded): On the training day the trainees having diagnosed the intra ocular bleed moved to a human cadaver to practise the canthotomy, the next stage is to trial the pig head model for the canthotomy as well as for the intra ocular bleed. Take home messages: With a little imagination and ingenuity an acceptable and inexpensive training aid for the emergency treatment of intra ocular bleed can be produced. Reference: Yung CW, Moorthy RS, Lindley D, Ringle M, Nunery WR. Efficacy of lateral canthotomy and cantholysis in orbital hemorrhage. Ophthal Plast Reconstr Surg. 1994;10(2):137–41